2008
DOI: 10.1007/s11999-007-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Work Satisfaction and Retirement Plans of Orthopaedic Surgeons 50 Years of Age and Older

Abstract: Retirement age and practice patterns before retirement are important for making accurate workforce predictions for orthopaedic surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 8 publications
2
21
0
1
Order By: Relevance
“…Several studies [7, 18, 22, 30, 31, 3639] examined the age that physicians expected to retire, and the age they actually retired (underlined in Table 4). The actual retirement age was found to be consistent with their expected retirement in all studies where the actual and expected retirement ages were jointly reported.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies [7, 18, 22, 30, 31, 3639] examined the age that physicians expected to retire, and the age they actually retired (underlined in Table 4). The actual retirement age was found to be consistent with their expected retirement in all studies where the actual and expected retirement ages were jointly reported.…”
Section: Resultsmentioning
confidence: 99%
“…This disillusionment was expressed by a sense of frustration with colleagues [38,39] feeling undervalued, lacking prestige [40,41] and a loss of interest in their work [42,44]. Medicolegal issues often arose from a lack of satisfaction with the regulation of medicine for reasons of unwelcome change, bureaucracy, oppressive management [40,42,43] and issues with physician partners [25,37]. Experiencing poor health, cognitive decline, difficulty sleeping and psychological distress were also factors leading to a physician's retirement [22,38,41,[45][46][47][48][49][50][51][52].…”
Section: Reasons For Retiring Earlymentioning
confidence: 99%
“…The decision to retire early was also linked to preserving one's health so they may lead a healthy retirement [38,42]. Financial issues contributing to a physician's early retirement included: increasing costs of retaining a practice, malpractice costs and other economic pressures, [15,39,43,45,53] insufficient financial remuneration and, pension security [42,50,54,55]. Several studies noted that physicians working in institutions or in countries where the policy landscape changed considerably were more inclined to retire because of perceptions around doctoring regulations and poor work satisfaction as a result of circumstances arising from the delivery of care [19].…”
Section: Reasons For Retiring Earlymentioning
confidence: 99%
See 2 more Smart Citations